BGA International Conference on Foundations innovations, observations, design and practice : proceedings of the international conference organised by British Geotechnical Association and held in Dundee, Scotland on 2-5th September 2003 - Newson, T. A. (Thomas Telford, 2003)
These conference proceedings comprise 94 papers from over 200 authors, and discuss state-of-the-art construction methods, numerical and analytical techniques, and laboratory tests for a broad range of foundation related problems.